Peningkatan Kompetensi Akademisi Melalui Pelatihan Menulis Abstrak Karya Ilmiah Untuk Publikasi International - Dewi Shinta Wulandari Lubis; Soraya Grabiella Dinamika (Yayasan Literasi Sains Indonesia, 2022)
Lecturers are an asset of a higher education institution that must be concerned for competitive advantage in facing the changing needs of education. Lecturers also have the obligation of the Tri Dharma of Higher Education, namely Teaching, Research, and Service. In research and service, lecturers need to publish articles both nationally and internationally. In an article that will be published, it must require them to write an abstract. The lecturers needed are competent and have certain competencies needed in order to support the implementation of the tri dharma of higher education. The problem seen is that there are still many lecturers who make mistakes in making abstracts in articles to be published. It is very important to be given the training to increase knowledge for lecturers to improve the quality of their article writing. One thing that can be done is the community service training activity entitled ‘Improving Lecturer Competence Through scientific training for international publication where participants in this activity consist of lecturers from Sekolah Tinggi Ilmu Manajemen (STIM) Sukma Medan. The method given is presentation, discussion, case study, and final evaluation. This activity aims to improve competence in writing abstracts of scientific papers. The result of this activity concluded that this activity was very helpful for participants in increasing their understanding and awareness in writing abstracts of scientific papers.